Modelagem comportamental como ferramenta de análise e projeto de um coletor de energia piezelétrico com investimento de energia controlado para busca do ponto de máxima coleta - Bortolin, Tales Luiz (2019)
Harvesting energy from vibrations by means of transducers is becoming a promising solution, within the context of IoT (Internet of Things), for supplying microsensor nodes and microcircuits. However, in order to extract electrical energy from the vibrations, piezoelectric transducers are necessary, which in turn convert the kinetic energy of the vibrations into electrical energy. For this, this work seeks to develop a vibrational energy collector, which consists of a switched inductor as low-loss energy transfer device, and functional modules required by the harvester for signal transformation and conditioning. Systematically, the various sensor modules of the system, necessary for the effective control of the energy harvesting process, are cataloged and the control variables are defined in function of these sensors by means of a control logic module described and modelled in Verilog-A language. The several modules used to build the energy harvester system (Energy-Harvester System) were simulated and its control verified. Simulation results showed the correct functioning of the system, the effect of the energy investment on the battery charging profile and the possibility of operating with maximum energy harvesting through the control of investment and harvesting times with the addition of an MPPT algorithm (Maximum Power Point Tracking).